Gestão democrática e eleição de diretores em escolas de educacão infantil: estudo de caso na rede municipal de Santa Maria/RS - Alves, Gilsilene Rony Pereira (2018)
This work was developed at Master’s Degree Course of Post-Graduation in Public Politics and Educational Management at Federal University of Santa Maria. The main object was to understand how the head teachers’ elections are held and how the actions in two schools of democratic management are made real. Theoretical foundation was based: on children education, in Ariès (2006) and Kuhlmann Jr. (2001, 2015); on democratic management, in Paro (2000, 2003, 2016), Dourado (2013, 2006a, 2006b), Ferreira (2000, 2001) and other authors related to the subject. Field research was made with qualitative approach, multiple choice type (GIL, 2008) with teachers, servants and staff in both schools. The research was developed through interviews and questions to the research subjects of City Education Net in Santa Maria/RS, showing how the process of democratic management and the election process of head teachers has worked. After analyzing and discussing the actions developed and the data collected, we noticed that the schools highlighted their conceptions about the democratic management and the election process of the head teachers. It was noticed that the teachers and the head teachers experience democracy in construction, for although they already have it as a right and duty, they still don’t experience it entirely. It was understood that as final product a study of change of the Law 4740/03 must be done in the democratic management of the City Net so that an item to it is added establishing the mandatory time of the head teachers this way assuring the right of having two consecutive mandates at most. So, a change at this law is urgent in order to contribute to the promotion of real democratic management.